Advances in the intraoperative delineation of malignant glioma margin - Jiang, Shan; Chai, Huihui; Tang, Qisheng (Frontiers in Oncology, 2023)
Surgery plays a critical role in the treatment of malignant glioma. However, due to the infiltrative growth and brain shift, it is difficult for neurosurgeons to distinguish malignant glioma margins with the naked eye and the preoperative examinations. Therefore, several technologies were developed to portray precise tumor margins intraoperatively. Here we introduced four intraoperative technologies to delineate malignant glioma margin, including magnetic resonance imaging, fluorescence-guided surgery, Raman histology, and mass spectrometry. By tracing their detecting principles and developments, we reviewed their advantages and disadvantages respectively, and imagined future trends.